KORELASI KETERAMPILAN MEMBACA PEMAHAMAN KARANGAN EKSPOSISI DENGAN KETERAMPILAN MENULIS KARANGAN EKSPOSISI - Sari, Fauza Puspita; Basri, Irfani; Ratna, Ellya (Universitas Negeri Padang, 2018)
The purpose of this research is (1) to know the level of reading comprehension skill of students exposition of class XI SMA Negeri 4 Pariaman, (2) to know the level of writing skill of exposition student of class XI SMA Negeri 4 Pariaman, (3) to know correlation of reading comprehension skill written exposition with the writing skills of exposition students of class XI SMA Negeri 4 Pariaman. This research type is quantitative research with correlation method. The results of this study are three, namely (1) reading comprehension skill of exposition is in BS qualification with M 87,07, (2) writing skill of exposition is in qualification B with M 84,66, and (3) there is significant correlation between the reading comprehension skills of the exposition essay with the writing skill of the exposition of the students of class XI SMA Negeri 4 Pariaman. Based on data analysis and discussion, in improving writing skill of exposition is required to read comprehension skill of exposition.Â Kata kunci: Korelasi, membaca pemahaman, karangan eksposisi, keterampilan menulis